IMPLEMENTASI PERATURAN DAERAH NOMOR 3 TAHUN 2013 TENTANG KAWASAN TANPA ROKOK (KTR) PADA KAWASAN DINAS KESEHATAN KOTA SEMARANG - Atmani W, Dimas Panji; Rahman, Amni Zarkasyi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The Government of Semarang City formed in beginning formed a Mayor Regulation Number 12 Year 2009 about No Smoking Area and restriced smoking area to overcome problem from the negative impact of cigaret, but that regulation is not proceed effective. At Last, goverment of Semarang City issued Local Regulation Number 3 Year 2013 about No Smoking Area (KTR). Based on finding from resercher, is known that the implementation of Local Regulation in Departement of Semarang City is not optimal and still found foul. The purpose of this research is to descripe the implementation of Local Regulation Number 3 Year 2013 about No Smoking Area, and to find out supporting and resistor factor in the implementation. This research is using descriptive qualitative with kualitative approach. Technique of collecting data that used are observation, interview, and documentation study. Based on the research, it can conclude that implementation of No Smoking Area in Departement oh Health of Semarang City has not been implemented optimally, so then, the government has to increase implementation at several point. Supporter factor of KTR implementation in Departement of Health Semarang City are communitacatin and authorizing signature, and Resistor factor are sources and birocration structure, so then need maximing supporter factor and minimizing resistor factor.